Ultrasound guided fine needle aspiration cytology (FNAC): an assessment of the diagnostic potential in histologically proven thyroid nodules - Branko Krišto; Ivana Vidović Krželj; Ana Krželj; Roberta Perković (Medicinski glasnik, 2022)
Aim: Results: of ultrasound guided fine needle aspiration cytology (FNAC) as the compatibility of cytological findings with histopathological diagnoses (the "gold standard") in the diagnosis of nodular thyroid lesions are inconsistent. The aim of this prospective study was to determine the validity of FNAC, as well as the compatibility of findings with histopathological diagnoses. Methods: The study included 92 patients who underwent FNAC and later surgery and histopathological assessment with a final diagnosis. Results: FNAC showed 95% specificity, 78% sensitivity and 90% accuracy. The compatibility of the cytological and histopathological findings was good (Kappa coefficient of 0.756; 95% CI). The cytology results proved to be very good at predicting malignant histopathological findings, (OR=72.33; p˂0.001). Also, the result of ROC analysis (AUC=0.866) confirmed FNAC as a very good method of distinguishing benign and malignant thyroid nodules. Conclusion: The results confirmed the correctness of the algorithm in which, following clinical or ultrasound confirmation of nodular thyroid lesions with suspicious changes, FNAC is indicated. The FNAC results should guide a clinician to further diagnostic and therapeutic procedures. Certainly, in case of suspected follicular/ Hurthle cell lesions one should be vigilant and aware of the fact that in these cases malignancy is defined by the invasion of blood vessels and/or the capsule, which FNAC is unable to detect.
Keywords: biopsy; cytopathology; fine-needle; histopathology